Local Food Security Analysis Based on Supply Chain Management: A Case Study of Rice Availability and Demand in Bojonegoro Regency in 2024 - Layalia, Aghnia; Mujanah, Siti; Fianto, Achmad Yanu Alif (PT Inovasi Pratama Internasional, 2025)
Objective– This study aims to analyze the balance between rice availability and rice demand across 28 districts in Bojonegoro Regency in 2024 by using the availability-to-demand (A/D) ratio as an indicator of local food security. Design/methodology/approach – Using a quantitative descriptive method, this study utilizes secondary data from the Central Statistics Agency (BPS) and the National Food Agency. The analysis includes rice production, population data, and consumption levels to calculate rice availability, rice demand, and A/D ratios in each district. Findings – The results show that 26 districts (92.86%) are in a rice surplus condition, while 2 districts (7.14%), Bojonegoro and Sekar are in deficit. Kalitidu district recorded the highest A/D ratio of 14.20, while Bojonegoro and Sekar had the lowest at 0.79 and 0.67 respectively. These disparities highlight the uneven spatial distribution of food availability. Research limitations/implications – This study focuses solely on rice as a staple food and uses regional-level data from Bojonegoro Regency in 2024. Future research can expand the scope to include other staple commodities and multiple time periods for longitudinal analysis. Practical implications – The A/D ratio serves as an effective tool for identifying surplus and deficit regions, which can inform local food distribution policies, emergency stock planning, and targeted agricultural development. Originality/value – This study contributes to the literature by applying the A/D ratio as a spatial indicator for food security assessment at the district level, offering practical insights for policymakers in managing surplus and deficit conditions more effectively.